Intertextuality in media discourse: A reader’s perspective - Velykoroda Yuriy; Moroz Oksana (ExELL (Explorations in English Language and Linguistics))
The article is a part of a research project on how intertextuality is perceived by readers of media texts. The focus of the article is on how intertextual references are recognized, interpreted, and substituted by EFL respondents. Based on the results of the survey, conclusions are drawn to address the following research questions – whether respondents can recognize intertextual references as such in the context, whether they can interpret an utterance despite failing to detect intertextual segments, and whether there exists a correspondence between recognizability of an intertextual reference and attempts at defining and/or replacing it. This paper is an attempt to empirically verify theoretical views on intertextuality. The results of the survey provide insights into how intertextuality is perceived by respondents.